Two-component rapid hardening material and preparation method thereof
Through the use of dual components to quickly hardening materials, the combination of polysexane and organic tin catalyst is used to solve the problem of slow and poor durability of existing water -based silicate penetration hardening materials, and realized faster hardening and more Good wear resistance and durability.
Patent Information
- Application Number
- CN202411059499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-04
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-04
AI Technical Summary
Existing aqueous silicate permeability hardening materials have problems of slow reaction speed and poor durability in improving the surface hardness and wear resistance of concrete.
It adopts a two-component rapid hardening material, which is composed of stable liquid polysilane (A component) and an organic tin catalyst (B component). Through the hydrolysis condensation reaction and the action of the catalyst, rapid solidification and the formation of a high-density structure are achieved.
A faster reaction rate and more significant wear resistance effect of penetration and hardening materials than water -based silicate, and have better durability and storage stability.
Smart Images

Figure BDA0004977425960000051 
Figure BDA0004977425960000061
Abstract
Description
Technical Field
[0001] The invention belongs to the surface treatment technology of cement-based materials, and in particular relates to a two-component fast-hardening material and a preparation method thereof. Background Art
[0002] In response to the increasing demands for wear-resistant, non-slip, beautiful and clean floors in current construction facilities, researchers at home and abroad have developed a variety of hardening materials for cement-based floors. By further enhancing the internal density of cement, they can reduce the problems of sanding and alkali efflorescence that are prone to occur in traditional cement-based floors.
[0003] At present, the main design ideas of hardening materials are divided into two categories: one is to use silicate solution as the main component, such as the patent document CN 202311409310.4, which uses potassium methyl silicate and sodium methyl silicate as the main components, and by adding additives such as nano-silica sol and modified graphene, the surface density, surface hardness, impermeability and durability of concrete building boards are improved, and the problems of looseness, dust and sand, and peeling are solved; the other is to use nano-silica sol as the main component, such as patent documents CN 201410172177.X and CN 201010543000.8, which disclose that silica sol is the main component, catalysts, surfactants and other additives are added, and it is directly sprayed on the concrete surface to achieve high wear resistance, high hardness, high water repellency, dustproof and other effects. The advantages of these two types of hardening materials are strong permeability and can quickly penetrate through the pores of concrete; but the effect on the surface is not strong, that is, the hardening reaction speed with cement is slow, making the overall cross-linked network structure of the surface not obvious. In addition, because it easily reacts with air or itself, resulting in a decrease in storage stability, the hardness and wear resistance of the concrete surface will gradually decrease with the extension of usage time, and the durability will be significantly deteriorated.
[0004] As the hardness and wear resistance of the ground in medium and heavy load industrial sites such as domestic factories, garages, and logistics storage bases are becoming increasingly high, the penetration hardening material products are required to have better stability, rapid hardening, and long-term durability. Therefore, developing a floor that can quickly improve the comprehensive performance of concrete substrates while meeting its durability requirements has become one of the research directions of various R&D personnel in this field. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a two-component fast-hardening material and a preparation method thereof.
[0006] In order to solve the above technical problems, the solution adopted by the present invention is:
[0007] Provided is a two-component rapid hardening material, which is composed of component A and component B; wherein:
[0008] Component A is a stable liquid polysilane, which is prepared by hydrolysis condensation reaction of silane, hydrogen ion donor, alcohol and appropriate amount of deionized water; wherein the mass ratio of silane: hydrogen ion donor: alcohol is 30-50: 0.0001-0.05: 1-3; hydrogen ion acceptor is also added during the reaction, and the hydrogen ion acceptor accounts for 3-5‰ of the mass of silane;
[0009] Component B is a catalyst mixed with organic tin, carbon-based compound and solvent, wherein the mass ratio of organic tin: carbonyl compound: solvent is 1:1:0-100.
[0010] As a preferred embodiment of the present invention, the silane contains at least one of the following alkoxy functional groups: tetraalkoxy functional group Si(OR1)(OR2)(OR3)(OR4), trialkoxy functional group Si(OR1)(OR2)(OR3)R4, dialkoxy functional group Si(OR1)(OR2)R3R4 or monoalkoxy functional group Si(OR1)R2R3R4, wherein R1, R2, R3, and R4 are hydrogen or an alkyl group of 1 to 16 carbon atoms.
[0011] As a preferred embodiment of the present invention, the hydrogen ion donor is one of HCl, H2SO4, HNO3, and CH3COOH.
[0012] As a preferred embodiment of the present invention, the alcohol is one of methanol, ethanol and isopropanol, or a mixture of two or all three.
[0013] As a preferred embodiment of the present invention, the hydrogen ion acceptor is one of CaCO3, Al(OH)3, and SrCO3.
[0014] As a preferred embodiment of the present invention, the organic tin is one of tetrabutyltin, dibutyltin diacetate and dibutyltin dilaurate.
[0015] As a preferred embodiment of the present invention, the carbon-based compound is one of dibenzoyl, benzophenone, benzoin, benzoin ethyl ether and benzoin butyl ether.
[0016] As a preferred embodiment of the present invention, the solvent is one of methanol, ethanol, isopropanol or a mixture of at least two of them.
[0017] The present invention further provides a method for preparing the aforementioned two-component rapid hardening material, comprising the following steps:
[0018] (1) weighing the raw materials of component A and component B according to the mass ratio;
[0019] (2) firstly take deionized water, alcohol, hydrogen ion donor, and silane and add them to the first reaction container in sequence, and stir at 300-800 rpm for 1-5 hours at an oil bath temperature of 40-90° C.; then add the hydrogen ion acceptor, change to condensation reflux at an oil bath temperature of 60-100° C., and keep stirring at 300-800 rpm for 4-12 hours to carry out hydrolysis and condensation reaction; after the reaction is completed, cool to room temperature, filter the product with filter paper to obtain the filtrate, which is component A, and seal it for later use;
[0020] (2) Add the organotin, carbon-based compound and solvent into a second reaction container, and stir at 200-500 rpm for 10-60 min at room temperature; the obtained mixed solution is component B, which is sealed for later use.
[0021] The present invention further provides a method for using the aforementioned two-component rapid hardening material, comprising the following steps:
[0022] (1) Carry out the construction and maintenance of concrete floor according to the requirements of the construction plan;
[0023] (2) At room temperature, mix the liquid of component A and the liquid of component B in a mass ratio of 97:3; then apply the mixture on the surface of the floor after curing, and the amount of the mixed liquid used is 10-20g / m2;
[0024] (3) Continue drying at room temperature for 8 hours to form a hardened material layer on the surface of the floor, and finally obtain a cement-based floor with a hardened material layer.
[0025] Compared with the prior art, the technical effects of the present invention are:
[0026] 1. The two-component fast-hardening material provided by the present invention has a faster reaction rate than the water-based silicate infiltration-type hardening material. The carbon-based compound in the present invention forms a cation under the influence of a hydrogen ion donor, and after losing water molecules, a stable cation can be formed, which reacts with an alcohol substance to generate a conjugate acid, and forms a catalyst to accelerate the reaction rate of the system. The catalyst can enable the silane in component A to react and solidify quickly, making the silane hydrolyzed more completely, and the 24h surface water absorption performance of the cement-based material better.
[0027] 2. The two-component rapid hardening material provided by the present invention has more significant wear resistance and better durability than water-based silicate penetrating hardening materials. Among them, component A is polysilane formed by hydrolysis and condensation reaction of silane, and component B is a catalyst. Components A and B are simply mixed and applied to the surface of cement-based materials. Under the action of the catalyst, polysilane accelerates its own polycondensation reaction while reacting with calcium hydroxide, calcium silicate hydrate, etc. in cement, and finally fills the surface pores of cement-based materials by forming high-density calcium silicate hydrate and silicon dioxide particles to form a high-density surface structure. Through the control of polysilane raw materials, reaction conditions and mass ratio with catalyst, the formed surface structure has excellent performance in hardness, glossiness, permeability and other aspects. Compared with water-based silicate penetrating hardening materials, two-component polysilane hardening materials do not introduce additional metal cations, reduce the possibility of surface alkali and alkali-aggregate reaction, and increase service life. In addition, the surface color of cement-based materials treated with polysilane does not change before and after treatment.
[0028] 3. The technical solution provided by the present invention is two-component separation and storage, and a hydrogen ion receptor neutralization reaction is added during the preparation of polysilane, and the hydrogen ions introduced by silane during the hydrolysis and condensation reaction are effectively removed through precise control. On the one hand, it prevents the hydrogen ions in the hardening material from reacting with the alkaline substances in the cement-based material to generate water, resulting in the formation of pores and the liberation of metal cations. On the other hand, it reconciles and balances the acid-base environment in the solution to keep the hydrolysis and condensation reaction of polysilane in a balanced state, preventing the increase in viscosity or even complete stagnancy caused by the irreversible curing reaction of polysilane. Compared with other organosilicon-based penetrating hardening materials, it has better storage stability, ensuring good permeability to cement-based materials after long-term storage, thereby steadily improving its performance and maintaining it continuously.
[0029] 4. The reaction mechanism of the present invention is different from the conventional two-component hardener that uses an organic tin catalyst to catalyze the hydrolysis and polycondensation of polysilane. The purpose of using an organic tin catalyst in conventional technology is to promote the reaction between silane and epoxy resin; while the purpose of adding an organic tin catalyst in the present invention is to accelerate the hydrolysis and condensation reaction of silane, so that the generated silane and concrete can react more fully, thereby accelerating the reaction rate of the hardening material and concrete, and at the same time having excellent properties such as high surface hardness and 24h surface water absorption. Therefore, the target of the catalyst and the corresponding technical effect achieved are different.
[0030] 5. The present invention can promote the reaction between components A and B by adding carbon-based compounds. Furthermore, by using hydrogen ion receptors to control the reaction rate, a hardener with long-term storage stability is obtained, which is specifically manifested in that the storage time can reach more than one year. Therefore, the product of the present invention can well meet the needs of transportation and storage at construction sites in remote areas. DETAILED DESCRIPTION
[0031] Part I Implementation of the Invention
[0032] 1. Components of two-component hardening materials:
[0033] The two-component rapid hardening material of the present invention is composed of component A and component B; wherein:
[0034] Component A is a stable liquid polysilane, which is prepared by hydrolysis condensation reaction of silane, hydrogen ion donor, alcohol and appropriate amount of deionized water; wherein the mass ratio of silane: hydrogen ion donor: alcohol is 30-50: 0.0001-0.05: 1-3; hydrogen ion acceptor needs to be added during the reaction, and the hydrogen ion acceptor accounts for 3-5‰ of the mass of silane; the silane contains at least one of the following alkoxy functional groups: tetraalkoxy functional group Si(OR1)(OR2)(OR3)(OR4), trialkoxy functional group Si(OR1)(OR2)(OR3)R4, dialkoxy functional group Si(OR1)(OR2)R3R4 or monoalkoxy functional group Si(OR1)R2R3R4, wherein R1, R2, R3, R4 are hydrogen or alkyl of 1-16 carbons. The alcohol is one of methanol, ethanol and isopropanol or a mixture of two or three. The hydrogen ion acceptor is one of CaCO3, Al(OH)3, and SrCO3.
[0035] The hydrogen ion donor is one of HCl, H2SO4, HNO3, and CH3COOH; when used, a diluted acid solution is used, and the mass of the hydrogen ion donor contained is converted according to the concentration of the acid solution.
[0036] Component B is a catalyst mixed with an organic tin, a carbon-based compound and a solvent, wherein the mass ratio of organic tin: carbonyl compound: solvent is 1:1:0-100. The organic tin is one of tetrabutyltin, dibutyltin diacetate and dibutyltin dilaurate. The carbon-based compound is one of dibenzoyl, benzophenone, benzoin, benzoin ethyl ether and benzoin butyl ether. The solvent is one of methanol, ethanol and isopropanol or a mixture of at least two of them.
[0037] Each reagent used in the present invention can be directly used as a commercially available reagent, or can be prepared according to existing public literature. The present invention does not make any special requirements on the preparation process of the reagent itself.
[0038] 2. Preparation method of two-component hardening material
[0039] In the present invention, the two-component hardening material is prepared according to the following steps:
[0040] (1) Weigh the raw materials of component A and component B according to the above-mentioned mass ratio;
[0041] (2) firstly take deionized water, alcohol, hydrogen ion donor, and silane and add them to the first reaction container in sequence, and stir at 300-800 rpm for 1-5 hours at an oil bath temperature of 40-90° C.; then add the hydrogen ion acceptor, change to condensation reflux at an oil bath temperature of 60-100° C., and keep stirring at 300-800 rpm for 4-12 hours to carry out hydrolysis and condensation reaction; after the reaction is completed, cool to room temperature, filter the product with filter paper to obtain the filtrate, which is component A, and seal it for later use;
[0042] (2) Add the organotin, carbon-based compound and solvent into a second reaction container, and stir at 200-500 rpm for 10-60 min at room temperature; the obtained mixed solution is component B, which is sealed for later use.
[0043] 3. How to use two-component hardening materials
[0044] As an example, the method for using the two-component hardening material in the present invention comprises the following steps:
[0045] (1) Carry out the construction and maintenance of concrete floor according to the requirements of the construction plan;
[0046] (2) At room temperature, mix component A liquid and component B liquid in a mass ratio of 97:3; then apply the mixture on the floor surface after curing, with the amount of the mixture used being 10-20g / m2;
[0047] (3) Continue drying at room temperature for 8 hours to form a hardened material layer on the surface of the floor, and finally obtain a cement-based floor with a hardened material layer.
[0048] Part II Examples and Comparative Examples
[0049] Examples 1-5 are all carried out in accordance with the contents described in the first part to prepare the hardened material. The process parameters of each example are shown in Table 1.
[0050] Table 1
[0051]
[0052]
[0053] Comparative Example 1
[0054] The infiltration nano-hardener comprises the following components in percentage by mass: 18.0% to 18.5% potassium methyl silicate, 48.0% to 48.5% sodium methyl silicate, 3% to 3.5% alcoholamine-modified graphene, 6% to 6.5% nano-Al2O3 sol and 0.5% to 1.0% surfactant, and the balance is deionized water; wherein the mass ratio of the alcoholamine to the graphene is 1:0.1 to 0.3.
[0055] Comparative Example 2
[0056] The commercially available hardener product model is PC-40, which includes two components, A and B; wherein, component A is composed of silane prepolymer, wear-resistant modified material, stabilizer and solvent; component B is composed of catalyst and solvent; the solvent in both components is ethanol.
[0057] Part III Performance Test and Result Analysis of Products in Examples and Comparative Examples
[0058] 1. Test methods
[0059] (1) Prepare mortar samples according to the provisions of JC / T2158-2021;
[0060] (2) According to the provisions of GB / T 22374-2018 "Floor Coating Materials", conduct the onset time and glossiness (60°) tests;
[0061] (3) According to the provisions of JC / T2158-202, the surface hardness, wear resistance and 24h surface water absorption tests are carried out.
[0062] 2. Test results and analysis
[0063] Based on the same test method, the performance test parameters of the products in Examples 1-5 and Comparative Examples 1-2 are shown in Table 2.
[0064] Table 2
[0065] sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Surface hardness 3.9 4.1 4.0 3.9 3.9 4.5 4.4 Wear resistance / mm(wear resistance) 0.01 0.002 0.005 0.01 0.002 0.01 0.015 Effective storage time 1 year or more 1 year or more 1 year or more 1 year or more 1 year or more 6 months 6 months Onset of Effect <10h <10h <10h <10h <24h 24h 24h Glossiness / ° 66 74 67 65 66 60 58 24h surface water absorption / mm 1.0 1.2 1.5 1.5 1.5 1.9 2
[0066] In Table 1, the onset time is the time to form a hardened material layer. The shorter the time, the faster the hardening speed. The smaller the value of the 24h surface water absorption, the better the waterproof and anti-penetration ability. It can be seen from the data in Table 1 that Examples 1-5 all show the best performance, mainly reflected in having higher surface hardness and wear resistance, and better 24h surface water absorption. Moreover, all examples have better performance than the control group.
Claims
1. A two-component fast-hardening material, characterized in that: It is composed of component A and component B; Component A is a stable liquid polysilane, which is prepared by hydrolysis condensation reaction of silane, hydrogen ion donor, alcohol and appropriate amount of deionized water; wherein the mass ratio of silane: hydrogen ion donor: alcohol is 30-50: 0.0001-0.05: 1-3; hydrogen ion acceptor is also added during the reaction, and the hydrogen ion acceptor accounts for 3-5‰ of the mass of silane; Component B is a catalyst mixed with organic tin, carbon-based compound and solvent, wherein the mass ratio of organic tin: carbonyl compound: solvent is 1:1:0-100.
2. The method according to claim 1, characterized in that The silane contains at least one of the following alkoxy functional groups: tetraalkoxy functional group Si(OR1)(OR2)(OR3)(OR4), trialkoxy functional group Si(OR1)(OR2)(OR3)R4, dialkoxy functional group Si(OR1)(OR2)R3R4 or monoalkoxy functional group Si(OR1)R2R3R4, wherein R1, R2, R3, and R4 are hydrogen or an alkyl group with 1 to 16 carbon atoms.
3. The method according to claim 1, characterized in that The hydrogen ion donor is one of HCl, H2SO4, HNO3, and CH3COOH.
4. The method according to claim 1, characterized in that: The alcohol is one of methanol, ethanol and isopropanol or a mixture of two or three thereof.
5. The method according to claim 1, characterized in that The hydrogen ion acceptor is one of CaCO3, Al(OH)3, and SrCO3.
6. The method according to claim 1, characterized in that The organic tin is one of tetrabutyltin, dibutyltin diacetate and dibutyltin dilaurate.
7. The method according to claim 1, characterized in that The carbon-based compound is one of dibenzoyl, benzophenone, benzoin, benzoin ethyl ether and benzoin butyl ether.
8. The method according to claim 1, characterized in that The solvent is one of methanol, ethanol and isopropanol or a mixture of at least two of them.
9. The method for preparing the two-component rapid hardening material according to claim 1, characterized in that: The following steps are involved: (1) weighing the raw materials of each component in component A and component B according to the mass ratio; (2) firstly take deionized water, alcohol, hydrogen ion donor, and silane and add them to the first reaction container in sequence, and stir at 300-800 rpm for 1-5 hours at an oil bath temperature of 40-90° C.; then add the hydrogen ion acceptor, change to condensation reflux at an oil bath temperature of 60-100° C., and keep stirring at 300-800 rpm for 4-12 hours to carry out hydrolysis and condensation reaction; after the reaction is completed, cool to room temperature, filter the product with filter paper to obtain the filtrate, which is component A, and seal it for later use; (2) Add the organotin, carbon-based compound and solvent into a second reaction container, and stir at 200-500 rpm for 10-60 min at room temperature; the obtained mixed solution is component B, which is sealed for later use.
10. The method for using the two-component rapid hardening material according to claim 1, characterized in that: The following steps are involved: (1) Carry out the construction and maintenance of concrete floor according to the requirements of the construction plan; (2) At room temperature, mix component A liquid and component B liquid in a mass ratio of 97:3; then apply the mixture on the floor surface after curing, with the amount of the mixture used being 10-20g / m2; (3) Continue drying at room temperature for 8 hours to form a hardened material layer on the surface of the floor, and finally obtain a cement-based floor with a hardened material layer.
Citation Information
Patent Citations
Aqueous concrete seal hardener and preparation method thereof
CN102030560B
Nano-silicon modified two-component wear-resistant penetrating hardener and preparation method thereof
CN103964737B
Penetrating nano hardener for plates and preparation method thereof
CN117447235A
Abrasion-resistant coating composition and coated article
CN101314698A
Concrete structure protection method
CN104343122A